Lessons Learned on the Operation of Learning Center for Smoke-Free Schools from Educational Institutions Certified as Learning Center Assessments - Kaewwongthi, Thuchchai; Kijmee, Patchareewan; Nimananth, Sukanya (Journal of Dhamma for Life, 2025)
This study aimed to investigate the operational methods of smoke-free school learning centers from educational institutions that have been certified as learning centers. The target groups consisted of 10 leading teachers from DoiSaket Wittayakom School, a model smoke-free school, and 3 administrators and leading teachers from Hang Dong Rathrathupathum School smoke-free school learning center. The research instruments were a checklist and interview recording form. Data were analyzed using content analysis and presented in a narrative format. The results revealed that the operational methods of the smoke-free school learning center at Hang Dong Rathrathupathum School covered all three assessment criteria areas: atmosphere and environment, personnel, and activities and processes, receiving 72 out of 75 possible points. The operational methods were divided into four aspects: 1) Planning - with clear policies from administrators, establishing management structures and issuing implementation orders according to the 7 measures for smoke-free schools 2) Implementation-defining clear roles and responsibilities, involving student leaders in organizing activities, developing staff expertise, and integrating tobacco education across all learning areas 3) Monitoring - key success factors identified included administrative support, clear policies, and participation from all sectors, while challenges included heavy teacher workloads and limited budget 4) Improvement - addressing teacher workload issues by integrating tobacco education into regular teaching, working as a team with clearly defined responsibilities, and mobilizing resources from network partners.